THE INFLUENCE OF A SHRINKAGE REDUCING ADMIXTURE ON THE LONG-TERM DEVELOPMENT OF DYNAMIC PROPERTIES IN ALKALI-ACTIVATED SLAG - Martin Alexa; Dalibor Kocáb; Barbara Kucharczyková; Jan Kotrla (Acta Polytechnica CTU Proceedings, 2019)
The paper investigates the way a shrinkage-reducing admixture affects the long-term development of dynamic properties in mortars made with alkali-activated slag (AAS). Two AAS mortars were tested - one contained a shrinkage-reducing admixture, the other did not. The specimens (prisms of 40 × 40 × 160mm) were observed for changes in the dynamic modulus of elasticity at ages of 3 days through 2 years using the ultrasonic pulse velocity test and the resonance method. Even though the statistical analysis of the results gave no proof that the shrinkage-reducing admixture affected the final values, the development of the elastic modulus appeared to follow a very interesting trend which is completely different from trends commonly observed in cement-based composites.